ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS MAKANAN DAN PELAYANAN RESTORAN GET STEAK DI KOTA MEDAN - Abdi, Fahmi Aditya; Nasution, Adelyna Oktavia; Harahap, Fauzi Syahputra; Siregar, Ummi Kalsum; Rahmadani, Nabila (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study highlights the comparison of customer satisfaction with two main aspects of restaurant services, namely food quality and service quality. The study was conducted at all branches of Get Steak Restaurant in Medan City with a quantitative approach. The results show that food quality received a more positive response than service, although both were in the "Good" category. Customers consistently appreciated the aspects of taste, presentation, and price suitability of food. Meanwhile, the service aspect still needs improvement, especially in terms of speed and consistency. This finding confirms that excellence in food quality needs to be balanced with improvements in service quality in order to create more optimal customer satisfaction.